Effect of six sigma on performance of medium scale manufacturing firms in south-eastern Nigeria - Okafor, Godwin Ikechukwu; Agbaeze, Emmanuel Kalu; Ekoja, Geoffrey Owoicho; Obamen, Joseph (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2018)
The effect of Six Sigma on Performance of MSFâs in South-East Nigeria. The main objective is to determine the effects of Six Sigma on the performance of MSFâs in South-East, Nigeria. While others are to: determine the extent at which process defines influence the customersâ patronage of their product, determine the extent at which process measurement influences product positioning and determine the extent at which improvement on production processes influence customers retention. The result shows that process definition practice among MSFâs significantly influenced customersâ patronage, process measurement among MSFâs was found significant influencing positioning and production improvement significantly influenced customer retention among MSFâs in South-East Nigeria. The study concluded adoption of Six Sigma practices positively influences the performance of the MSFâs in South-East Nigeria.